Ordnance Survey Illustrated Atlas of Victorian & Edwardian Britain - Published by The Automobile Association (London The Automobile Association, 1991)
Early in the century, Ordnance Survey published their first-ever atlas, which showed Britain at a scale of a quarter of an inch to the mile. This is a reproduction of it, to celebrate the bicentenary of OS. High-quality scanning methods have been used, and the book offers an insight into how Britain has changed. It is illustrated with photographs from the Francis Firth collection - a huge archive of images of towns and villages throughout the country, taken by Firth and his photographers during the late-19th and early-20th century. The text covers social, economic and geographical aspects of Victorian and Edwardian Britain.
Includes Colored Illustration, Map and Index.
Keywords: Great Britain -- Economic conditions -- 19th century -- Maps